"Swinging on a Pendulum": Armenia in the Eurasian Economic Union and With the European Union. Issue 1 (2nd January 2017) - Vasilyan, Syuzanna
Abstract : The article aims to explain Armenia's foreign policy shift from its pre-signature of the Association Agreement (AA)/Deep and Comprehensive Free Trade Area (DCFTA) with the European Union (EU) in favor of joining the Customs Union (CU)/Eurasian Economic Union (EEU). It uncovers the factors in different policy spheres by examining data and scores, and draws on public opinion to investigate whether it was in sync with the presidential announcement. While Armenia is "swinging on a pendulum, " the study considers the challenges of being a member of the EEU and the repercussions for the country's relations with the EU.